Development of Student Worksheets Based on Contextual Teaching and Learning (CTL) on Heat Transfer - Mudalfy Etyanna Nurazri; Faizatul Mabruroh; Yulia Tri Samiha; Apit Fathurohman (Jurnal Pembelajaran Fisika, 2022)
This research had a purpose to result in student's activity sheet based on contextual teaching and learning toward the movement of heat subject that validate, practical. The research method was used to develop on 4d model. This research held on even semester in 2019 experts validated show that the student's activity sheet had been fulfilled valid criteria with 84.583% for material and design aspect is 82.5%. The small group trial resulted in an average value of 91, 18%. The result of this research showed that students' activity sheets based on contextual teaching and learning toward the movement of heat subjects had fulfilled valid criteria.Keywords: Student's activity sheet based, Contextual Teaching and Learning movements of heat subject.DOI: http://dx.doi.org/10.23960/jpf.v10.n1.202212